Partiti populisti, diritti e uguaglianza di genere - Macaluso, Marilena (SocietàMutamentoPolitica, 2021)
The Great Recession changed the political landscape of the European democracies with the electoral success of populist protest parties in different countries. In this article, we wonder if there are features that characterized these political parties about the issues of gender equality and women’s rights. Populism and feminization of politics are recurring topics in the scholars’ debate, but the relationships between these two phenomena are still little studied. Seeing as the issue is linked to context, and not only to the political parties’ differences, we will focus on three illustrative cases, in different European nations – Spain, Finland, Poland – analysing scientific literature and documents. The hypothesis is that the issues of gender can be an additional contentious line useful for defining identity and differences in the heterogeneous set of populist parties.